Women Resistance in Kahlil Gibran’s Novel, Broken Wings - Idris; Henrikus Joko Yulianto (Syntax Corporation, 2026)
This research examines the portrayal of women’s resistance in Kahlil Gibran's novelette, Broken Wings, through the lens of ecofeminism. Ecofeminism believes that women and environmental exploitation cannot be separated. Both emerge from patriarchal structures that upheld dominance and oppression. The purpose of this study is to analyze how the environment is constructed, how the oppression against women is depicted, and how resistance is represented in the narrative in the novelette Broken Wings. The study used descriptive qualitative analysis using Susan Griffin’s cultural ecofeminism as the theoretical framework to analyze the novelette. The findings reveal that male supremacy over women and nature is persistently portrayed, with Selma's character embodying subtle yet significant resistance. Her suffering, confinement, and resilience are symbolically reflected in natural images such as gardens and seasons. The study concludes that Selma's resistance manifests not through open rebellion but through inner resilience, emotional strength, and self-awareness, challenging the notion that silent women within oppressive systems are entirely passive. Thus, Broken Wings not only critiques gender-based discrimination but also highlights an integrated environmental awareness, confirming the ecofeminist argument that the domination of women and nature stems from the same patriarchal forces.